A cohort analysis of the perceived market potential of thanatourism in Malaysia - Christy, Bidder; Boyd, Sun Fatt; Spencer, Hedley Mogindol (GADING Journal for the Social Sciences, 2024)
Thanatourism has experienced significant growth, both in terms of its commercial potential and scholarly attention. In Malaysia, the government has expressed interest in developing thanatourism as a source of tourism revenue and a means of preserving the nation’s history and heritage. However, despite the increasing commercial interest and the considerable potential of thanatourism in the country, there is a notable lack of scholarly research, particularly concerning the market potential of thanatourism in Malaysia from a local perspective, and across different generational cohorts. In response to this gap, the present study seeks to advance the literature on thanatourism within the Malaysian context by examining local residents’ understanding, acceptance, and perception of the market potential of thanatourism, through the lens of generational cohorts. This was achieved via a quantitative, descriptive, cross-sectional study. The research sample comprised Malaysian adults aged 18 and above, with data collected through online surveys. A total of 356 responses were analysed using descriptive analysis, independent-samples t-test, and Eta squared statistical tests. The key findings indicated that both older and younger participants had prior exposure to thanatourism but lacked a comprehensive conceptual understanding of the phenomenon. Younger participants tended to associate thanatourism with supernaturalism, as their primary source of knowledge stemmed from entertainment-focused, technology-driven social media platforms. They also demonstrated greater enthusiasm and acceptance of thanatourism, with a more optimistic view of its market potential. Furthermore, both older and younger participants ranked education as a key reason for the development of thanatourism in Malaysia. However, their secondary motivations differed: older individuals prioritised commemoration, whereas younger individuals favoured entertainment. Theoretically, the study contributes to the body of literature on thanatourism in Malaysia by offering generational insights into this niche area of tourism. Practically, it provides an understanding of how local residents perceive thanatourism, which in turn assists in gauging their level of acceptance towards the sustainable development of this tourism sector in the country. Based on the study’s findings, future research may explore the role of religious or traditional beliefs in shaping individuals' acceptance of thanatourism and their perceptions of its market potential.